Canagliflozin Inhibits Human Endothelial Cell Proliferation and Tube Formation - Behnammanesh, Ghazaleh; Durante, Zane E.; Peyton, Kelly J.; Martinez-Lemus, Luis A.; Brown, Scott M.; Bender, Shawn B.; Durante, William (Frontiers in Pharmacology, 2019)
Recent clinical trials revealed that sodium-glucose co-transporter 2 (SGLT2) inhibitors significantly reduce cardiovascular events in type 2 diabetic patients, however, canagliflozin increased limb amputations, an effect not seen with other SGLT2 inhibitors. Since endothelial cell (EC) dysfunction promotes diabetes-associated vascular disease and limb ischemia, we hypothesized that canagliflozin, but not other SGLT2 inhibitors, impairs EC proliferation, migration, and angiogenesis. Treatment of human umbilical vein ECs (HUVECs) with clinically relevant concentrations of canagliflozin, but not empagliflozin or dapagliflozin, inhibited cell proliferation. In particular, 10 μM canagliflozin reduced EC proliferation by approximately 45%. The inhibition of EC growth by canagliflozin occurred in the absence of cell death and was associated with diminished DNA synthesis, cell cycle arrest, and a striking decrease in cyclin A expression. Restoration of cyclin A expression via adenoviral-mediated gene transfer partially rescued the proliferative response of HUVECs treated with canagliflozin. A high concentration of canagliflozin (50 μM) modestly inhibited HUVEC migration by 20%, but markedly attenuated their tube formation by 65% and EC sprouting from mouse aortas by 80%. A moderate 20% reduction in HUVEC migration was also observed with a high concentration of empagliflozin (50 μM), while neither empagliflozin nor dapagliflozin affected tube formation by HUVECs. The present study identified canagliflozin as a robust inhibitor of human EC proliferation and tube formation. The anti-proliferative action of canagliflozin occurs in the absence of cell death and is due, in part, to the blockade of cyclin A expression. Notably, these actions are not seen with empagliflozin or dapagliflozin. The ability of canagliflozin to exert these pleiotropic effects on ECs may contribute to the clinical actions of this drug.